PENGARUH EVA, EARNINGS, ARUS KAS OPERASI, DAN RESIDUAL INCOME TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2014-2016 - Filiana Filiana; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study is to examine the effect of economic added value,earnings before extraordinary items, cash flow from operations and residualincome to stock returns. The population in this study is a manufacturing companylisted on the Indonesia Stock Exchange period 2014-2016. Sampling technique inthis research using purposive sampling method and obtained 23 manufacturingcompanies listed in Indonesia Stock Exchange period 2014-2016. Source of datafrom this research comes from Indonesia Stock Exchange (IDX), www.idx.co.id.The method of analysis used in this study is the classical assumption test,hypothesis test and multiple linear regression test.The results of this study indicate that: (1) Based on the simultaneous testor F test. Then the economic value added variable, the earning beforeextraordinary item, the cash flow from the operation and residual incomesignificantly influence the stock return. (2) Economic value added variable,earnings before extraordinary item, cash flow from operation and residual incometogether influencing 41% to return received by shareholder of manufacturingcompany listed on BEI and 59% explained by other variable which is not includedin this research model. (3) Partially residual income variable has a significantnegative effect on stock return. While economic value added variable, earningsbefore extraordinary item, cash flow from operation have a significant positiveeffect to stock return.Keywords: economic value added, earnings before extraordinary item, operatingcash flow, residual income and stock return